'Normal' and 'failing' mothers: Women's constructions of maternal subjectivity while living with multiple sclerosis. (September 2019) - Parton, Chloe; Katz, Terri; Ussher, Jane M
Multiple sclerosis causes physical and cognitive impairment that can impact women's experiences of motherhood. This study examined how women construct their maternal subjectivities, or sense of self as a mother, drawing on a framework of biographical disruption. A total of 20 mothers with a multiple sclerosis diagnosis took part in semi-structured interviews. Transcripts were analysed using thematic decomposition to identify subject positions that women adopted in relation to cultural discourses of gender, motherhood and illness. Three main subject positions were identified: 'The Failing Mother', 'Fear of Judgement and Burdening Others' and 'The Normal Mother'. Women's sense of self as the 'Failing Mother' was attributed to the impact of multiple sclerosis, contributing to biographical disruption and reinforced through 'Fear of Judgement and Burdening Others' within social interactions. In accounts of the 'Normal Mother', maternal subjectivity was renegotiated by adopting strategies to manage the limitations of multiple sclerosis on mothering practice. This allowed women to self-position as 'good' mothers. Health professionals can assist women by acknowledging the embodied impact of multiple sclerosis on maternal subjectivities, coping strategies that women employ to address potential biographical disruption, and the cultural context of mothering, which contributes to women's experience of subjectivity and well-being when living with multiple sclerosis.